An Analysis of Students’ Writing Past Conditional Sentence in Kabupaten Tangerang - Adela, Cahya; Suharti, Dwi Sloria; Hanim, Imtihan (Universitas Mathla'ul Anwar Banten, 2020)
Writing English as a Foreign Language (EFL) requires one to applied writing rules such as language features: vocabulary, punctuation, type of text, text organization as well as appropriate Grammar, especially Past Conditional sentences. It is desired as a rule to convey one's expectations in their daily activities. The purpose of this research was to describe the difficulties and the factors that students of one of SMAN in Kabupaten Tangerang faced in writing using Past Conditional Sentence. The approach applied in this research was qualitative, and the method used in this research was descriptive analysis. Written tests and interviews were used to collect the data. The results of this research discovered the problems faced by students in writing using the Past Conditional Sentence. It was found that 73% of students had the same writing problem using past conditional sentences. The common mistakes were Verb and Auxiliary's wrong usage and incorrect application of Past Conditional formulas. Furthermore, it was revealed that the problems of language factors contribute to writing related to environmental, linguistics, and psychological factors.